Glycaemic chorea. Issue 5 (8th May 2017) - Dalen, Chani Tromop-van; Bourke, David; Rosemergy, Ian
Abstract : Objectives: To describe a case of glycaemic chorea and review the literature. Case: A 70-year-old Maori woman with type 2 diabetes was seen at Wellington hospital following a fall and two days of fluctuating bilateral leg weakness. A full neurological examination was normal. Random blood glucose levels were 22.9 and 18.8 mmol with an HbA1c of 101 mmol/mol. She had stopped metformin and gliclazide 40 days earlier. They were restarted. Three weeks later she re-presented with persistent bilateral leg weakness, which recovered over three days with physiotherapy. Blood glucose levels were 5.1–8.4 mmol/L. She had one hypoglycaemic episode (3.6 mmol/L). On the fourth day of admission she developed intermittent hemichorea involving the right upper limb. Over one week this became constant and then spread to both upper and lower limbs. MRI brain showed bilateral T1 hyperintensities within the lentiform nuclei. She was treated with haloperidol, sodium valproate and stabilisation of blood glucose levels between 8 and 12 mmol. Her chorea improved over 5 days, resolving after one month. Conclusions: Both hyperglycaemia and hypoglycaemia can rarely cause chorea 1 . The condition is more common in older women with type 2 diabetes 2 . Typical findings on brain MRI are of basal ganglia T1 hyperintensity, which can be unilateral or bilateral and almost always involves the putamen 2 . Chorea and MRI changes usually resolve on stabilisation of glucose levels but symptoms can persist 1, 2, 3 . Dopamine-receptor antagonists can be used if symptoms do not resolve with stabilisation of blood glucose alone 1, 3 . We propose glycaemic chorea as a name for this condition, given it can occur with hyper or hypoglycaemia 1 and in the setting of ketoacidosis 4 Glycaemic chorea is a rare, but important complication of diabetes. This patient's chorea could have been caused by hyper or hypoglycaemia.